Ammonia-induced CuO/13X for H2S removal from simulated blast furnace gas at low temperature - Erping Cao; Yuhua Zheng; Hao Zhang; Jianshan Wang; Yuran Li; Tingyu Zhu; Zhan-guo Zhang; Guangwen Xu; Yanbin Cui (Green Energy & Environment)
Blast furnace gas (BFG) is an important by-product energy for the iron and steel industry and has been widely used for heating or electricity generation. However, the undesirable contaminants in BFG (especially H2S) generate harmful environmental emissions. The desulfurization of BFG is urgent for integrated steel plants due to the stringent ultra-low emission standards. Compared with other desulfurization materials, zeolite-based adsorbents represent a viable option with low costs and long service life. In this study, an ammonia-induced CuO modified 13X adsorbent (NH3–CuO/13X) was prepared for H2S removal from simulated BFG at low temperature. The XRD, H2-TPR and TEM analysis proved that smaller CuO particles were formed and the dispersion of Cu on the surface of 13X zeolite was improved via the induction of ammonia. Evaluation on H2S adsorption performance of the adsorbent was carried out using simulated BFG, and the results showed that NH3–CuO/13X-3 has better breakthrough sulfur capacity, which was more than twice the sulfur capacity of CuO/13X. It is proposed that the enhanced desulfurization performance of NH3–CuO/13X is attributed to an abundant pore of 13X, and combined action of 13X and CuO. This work provided an effective way to improve the sulfur capacity of zeolite-based adsorbents via impregnation method by ammonia induction.